THE INFLUENCE OF WORK ENVIRONMENT, WORK DISCIPLINE AND MOTIVATION ON EMPLOYEE PERFORMANCE - Robert, Robert; Adiputra, I Gede (International Journal of Application on Economics and Business, 2024)
The aim of this study is to determine the influence of the work environment, work discipline, and work motivation on the performance of employees at CV Jf United. This study employs quantitative methodologies, utilizing surveys and library data as data collection approaches. The study sample consisted of 81 employees from Cv. Jf United, selected using the saturated sample approach. The data analysis technique involved utilizing smartPLS software as a tool for data processing. Penluis utilizes structural equation model (SEM) approaches for data analysis, which are categorized as outer models for assessing validity and dependability, and inner models for analyzing the data. In addition, the data analysis technique utilizes the Path analysis model. The results of this study suggest that the work environment, work discipline, and work motivation have a significant influence on employee performance. Work discipline is the primary factor that significantly impacts employee performance.